Villette - d uthor.9; Smith, Margaret, 1931-; Rosengarten, Herbert (Oxford : Oxford University Press, 2020)
This work features the definitive Clarendon edition of 'Villette', which is sourced from the earliest printings of Bronte's work. The text is supplemented with a commissioned introduction, which gives a thorough and in-depth analysis of the context.
This edition previously issued in print: 2000.
Includes bibliographical references.
Description based on print version record and publisher information.
Keywords: Belgium -- Social life and customs -- 19th century -- Fiction